Latency-Associated Nuclear Antigen (LANA) Promotes Ferroptosis by Suppressing Nrf2/GPX4 and Upregulating MDM2 - Yuejia Cao; Shihan Shao; Yingying Zhang; Dandan Song; Fei Gui; Xinyi Chen; Yu Hong; Rong Chen; Yang Song; Dongmei Li; Xiaohua Tan; Chunhong Di (Pathogens, 2025)
Ferroptosis, an iron-dependent cell death driven by lipid peroxidation, is regulated by key mediators including glutathione peroxidase 4 (GPX4) and nuclear factor erythroid 2-related factor 2 (Nrf2). Kaposi’s sarcoma-associated herpesvirus (KSHV) encodes latency-associated nuclear antigen (LANA), a multifunctional protein critical for viral persistence. Although studies reported that KSHV infection enhanced cellular resistance to ferroptosis, the specific role of LANA in this process remains unexplored. Here, we demonstrate that LANA unexpectedly promotes ferroptosis. In KSHV-positive iSLK.219 cells, LANA knockdown significantly attenuated RSL-3-induced ferroptosis, whereas LANA overexpression sensitized HeLa cells to ferroptotic death. Quantitative analysis revealed that LANA-depleted cells exhibited significantly elevated ROS accumulation (p < 0.01), whereas LANA-overexpressing cells maintained reduced ROS levels during challenge with the ferroptosis inducer RSl-3. Mechanistically, LANA suppressed glutathione peroxidase 4 (GPX4) expression, reduced nuclear factor erythroid 2-related factor 2 (Nrf2) expression and impaired its nuclear translocation, and upregulated mouse double minute 2 homolog (MDM2) expression. Pharmacological inhibition of Nrf2 (ML385) or MDM2 (nutlin3a) reversed the ferroptotic effects of LANA knockdown or overexpression, respectively. These findings reveal a pro-ferroptotic role of LANA via Nrf2/GPX4 suppression and MDM2 activation.